Hubungan Pola Pemberian MPASI Dengan Status Gizi Balita Usia 6 – 24 Bulan Di Desa Paron Kecamatan Ngasem Kabupaten Kediri - Anggraeni, Enggar; Herawati, Annastasya; Palupi, Mirthasari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Toddlers between 6 to 24 months of age are given complementary foods, or complementary foods, which help to fulfill their nutritional needs. Complementary feeding should be given according to the guidelines, which are simple, inexpensive, high in protein, energy, and micronutrients. The UFREJUTEK VARES BERSIH (Age, Frequency, Amount, Texture, Variety, Response, Cleanliness) principle is a supplementary feeding guide that has four stars and one menu. This study was conducted in Paron Village, Ngasem Sub-district, Kediri District, using a cross-sectional research design and chi-square research methodology. Samples were taken randomly or using random sampling techniques. A total of 40 mothers who have children aged between 6-24 months became the research sample. Based on the results of the study, 90% of toddlers have normal nutritional status (-2 SD + 1 SD), while 10% of toddlers have a nutritionally deficient status (<-2 SD). A total of 72.5% had poor complementary feeding patterns and 27.5% had good complementary feeding patterns. The p-value was 0.906 (p-value>0.005), indicating that there was no association between complementary feeding patterns and the nutritional status of children under five, based on the results of statistical tests investigating the relationship between the two.